Aristolochia vuquangensis (Aristolochiaceae), a new species from Central Vietnam - Do, Truong Van; Nguyen, Hung Viet; Le, Khuong Duy (Phytotaxa, 2021)
Aristolochia vuquangensis (Aristolochia subgenus Siphisia), a new species from Central Vietnam, is described and illustrated here. This species is most similar to A. wardiana and A. forrestiana by sharing an ovate to lanceolate-ovate leaf blade and a cylindric or saccate-shaped limb, but it differs principally from the two species in having a densely brown hirsute outer surface of perianth, an oblong-ovate utricle, 1.1–1.5 cm long, an unequally semicircular 3-lobed limb in pre-anthesis, with a revolute median lobe, larger than two lateral lobes, abaxially concave, and lower one-third of the inner surface of limb densely covered by trichomes. A detailed description, illustrations, information on ecology, conservation status, and comparison with two similar species are also provided.